(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the impact of globalization processes on the mahalla institution and its role in preserving national values, traditions, and cultural heritage. In the context of global cultural influences, the study highlights the socio-cultural functions of the mahalla and its importance in transmitting customs and traditional values from generation to generation. Special attention is paid to the transformation of the mahalla institution in the contemporary global environment, its potential in maintaining national identity, and the challenges it faces. The article presents scholarly conclusions and recommendations aimed at strengthening the role of the mahalla in preserving national cultural heritage and ensuring social stability